Análisis de la percepción auditiva de la modalidad declarativa e interrogativa en el español hablado en Medellín - Muñetón-Ayala, Mercedes Amparo (2025)
This work subjects the re-synthesized intonational contours of declarative and absolute interrogative sentences uttered by Medellin residents to a perceptual analysis by 67 participants from the same locality. The perception of the modality is analyzed based on the sex of the speaker and the listener, as well as on the accentual typologies, considering both accuracy rates and reaction times. The results show that Medellin residents identify declarative and interrogative sentences with over 65% accuracy. In general, accuracy was higher in declaratives than in interrogatives, but reaction times showed the opposite pattern. Specifically, declarative sentences with proparoxytone accentual typology and interrogative sentences with paroxytone accentual typology are better perceived than those with the other typologies. Likewise, female voices, in contrast to male voices, are associated with increased perceptual performance in the interrogative modality.